Shrimp Waste Fermentation by Isoptericola sp. Strain A10-1 as Feed Compound for Improve Yield Carcas and Performance of Magelang Duck - Prasetyo, Amrih (2016)
Shrimp waste utilization as feed in an effort to reduce environmental pollution and the greenhouse effect. Magelang ducks which are a source of germplasm Indonesia. The purpose of this study was the use of fermented shrimp waste by Isoptericola sp. bacteria chitin biodegradation as duck feed compound to improve the performance and carcass quality. The study consisting of 7 treatment feed R0 = concentrate feed as a control, R= shrimp waste non fermented (SWNF) 5%, R2= (SWNF) 10%, R3 = (SWNF) 15%, R4 = shrimp waste fermentation (SWF) 5%, R5 = (SWF) 10% and R6 = (SWF) 15%, each repeated 5 replicates in 4 enclosure floc (7x5x4) = 140 ducks. Feed and water given adlibitum. The research result is specific activity chitinase incubation at pH 8, arter 5 days (0.70 U/mg) as inoculum. The addition of shrimp waste fermentation level 5, 10, and 15% did not differ significantly on the performance of Magelang ducks ie live body weight, carcass percentage, body weight gain and feed conversion, but also does not degrade the performance of Magelang ducks. The dry matter intake and organic matter intakes showed significantly.